(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information on effective mechanisms for developing students’ intellectual fields, certain principles of modular teaching technologies (modularity, structuring of educational materials based on mutual compatibility, dynamic nature, implementation of an active approach, compatibility principles). Also, didactic processes, didactic games and problem assignments aimed at systematic development of students’ intellectual spheres were discussed.